A histone K-lysine acetyltransferase CqKAT2A-like gene promotes white spot syndrome virus infection by enhancing histone H3 acetylation in red claw crayfish Cherax quadricarinatus. (June 2020) - Liu, Ling-ke; Gao, Rui-lin; Gao, Yan; Xu, Jiao-yang; Guo, Li-mei; Wang, Ke-jian; Liu, Hai-peng
Abstract: In contrast to that hypoacetylation of histones is associated with condensed chromatin and gene silencing, the hyperacetylation of histones can promote an "open chromatin" conformation and transcriptional activation, which is recruited by some viruses to enhance the viral genome replication in host cells. However, the function of histone acetylation modification in the infection of white spot syndrome virus (WSSV), one of the most virulent pathogens for crustaceans like shrimp and crayfish at present, is still unknown. Previously, we found that the transcript of a histone K-Lysine acetyltransferase CqKAT2A-like gene was down-regulated in a differentially expressed transcriptome library of the haematopietic tissue (Hpt) cells from red claw crayfish Cherax quadricarinatus upon WSSV infection at 12 hpi. To further reveal its possible role in anti-WSSV response, CqKAT2A-like gene was then identified with an open reading frame (ORF) of 2523 bp encoding 840 amino acids, which contained a conserved PCAF-N domain, acetyltransf1 domain and bromo domain. Gene expression analysis showed that CqKAT2A-like was distributed in all tissues examined with high presence in haemocyte and muscle, and the transcript was significantly down-regulated after WSSV infection in Hpt cells. Furthermore, the level of histone H3 acetylation (H3ac) was strongly reduced by gene silencing of CqKAT2A-like, which was accompanied with the significantly decreased gene expression of WSSV in Hpt cells, suggesting that CqKAT2A-like gene can promote the activity H3ac and the replication of WSSV. When the H3ac was induced by histone deacetyltransferase inhibitor TSA, the transcription of WSSV genes including both IE1 and VP28 genes was significantly increased, indicating that H3ac participated in WSSV infection in Hpt cells. Taken together, these data suggest that CqKAT2A-like gene might promote the replication of WSSV by regulating H3ac, which sheds new light on the pathogenesis of WSSV in crustaceans. Highlights: CqKAT2A-like may promote the transcription of WSSV by enhancing histone H3 acetylation modifications. Histone H3 acetylation may promote the transcription of WSSV. CqKAT2A-like and histone acetylation modifications may provide new strategy against white spot disease.